Granuloma pyogenicum in the rare location on the posterior vaginal wall - Rotsztejn, Helena; Krawczyk, Tomasz; Raczkowska, Zofia; Kulig, Andrzej; Szpakowski, Marian (Menopause Review/Przegląd Menopauzalny, 2007)
The authors present a case of rare location of pyogenic granuloma on the posterior vaginal wall in a 71-year-old woman.